KENDALA ADAPTASI PEMERINTAH DAERAH DALAM IMPLEMENTASI DAK FISIK SAAT PANDEMI COVID-19 - Andi Setyo Pambudi (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2021)
The COVID-19 pandemic affects not only the implementation of central government policies, but also local governments. Special transfer funding mechanisms such as physical DAK, which are central government funds implemented by local governments according to national priorities, are not without obstacles. Since the beginning of COVID-19 entering Indonesia, the central government has anticipated not optimal development processes funded by DAK Fisik by issuing various policy packages, both refocusing and relaxing budget disbursements. From the local government side, implementation at the field level must still be demanded optimally even though on the way it has to deal with regulations related to COVID-19 which often hinder the achievement of targets. The adaptation of local governments in the development process during the COVID-19 pandemic is an interesting thing to explore further. The method used in this research is a mixed method approach through online survey-based analysis, literure reviews and virtual discussions. This study aims to provide information on the adaptation constraints of local governments in implementing DAK Fisik during the COVID-19 pandemic as input for better DAK planning from the perspective of field implementers. The results of the analysis encourage the importance of consideration and involvement of local governments and regional characteristics in DAK planning, with the hope that development can be implemented better, more recent and adaptive, including during emergencies. Keywords: online survey, DAK, COVID-19, Local Governments